PENGARUH VIDEO PEMBELAJARAN BIOLOGI TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA PADA MATERI SISTEM PEREDARAN DARAH KELAS XI MAS. AL-IHSAN PANDEGLANG - Haerani, Yeni; Rina Nuraisyah; Hermawan (Jurnal Biogenerasi, 2026)
Biology learning often involves abstract concepts, such as the circulatory system, which students find difficult to understand through conventional methods. This study employed a quasi-experimental design with a quantitative approach. A sample of 42 eleventh-grade students from MAS Al-Ihsan Pandeglang was divided into an experimental group, which used video media, and a control group, which used conventional methods. Data were collected through motivation questionnaires and multiple-choice tests. The results showed that the experimental group achieved a significantly higher average N-Gain score of 56.50%, compared to 21.25% for the control group. Furthermore, student motivation was high, with 93.21% of students exhibiting a positive attitude toward the use of learning videos. In conclusion, the use of biology learning videos significantly enhances both student motivation and learning outcomes regarding the circulatory system materiallearning outcomes and motivation compared to conventional methods.